Analyzing the Present Sustainability of Turkey's Current Account Position - Ayla Oğuş; Niloufer Sohrabji (Izmir University of Economics, Department of Economics, 2008)
In this paper we assess the present sustainability of Turkey's current account position using the framework provided by Milesi-Ferretti and Razin (1996) based on the ability-to-pay and willingness-to-lend model. This framework allows us to assess the structural features and macroeconomic policy indicators. We extend this framework by considering global sustainability indicators as well. Using data for three periods, 1991-1993, 1998-2000 and 2004-2006 we evaluate the present sustainability in light of the prior two crises (1994, 2001). Based on our analysis of these factors in the extended framework, we conclude that Turkey's internal structure and macroeconomic conditions (such as exports and the fiscal position) have improved that are allowing Turkey to continue having large and increasing current account deficits. However, there is vulnerability from global factors namely the impending U.S. recession and a potential global slowdown. This might require some adjustments in policy to continue accumulating large deficits.
Keywords: F32; F41; 330; Current account sustainability; predictors of crisis; Turkey; Leistungsbilanz; Außenwirtschaftliches Gleichgewicht; Wirtschaftskrise; Türkei